2017
DOI: 10.1002/ajp.22665
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness enhances long‐term event memory in non‐human primates, irrespective of reinforcement

Abstract: Non-human primates are capable of recalling events that occurred as long as three years ago, and are able to distinguish between similar events; akin to human memory. In humans, distinctiveness enhances memory for events, however, it is unknown whether the same occurs in non-human primates. As such, we tested three great ape species on their ability to remember an event that varied in distinctiveness. Across three experiments, apes witnessed a baiting event in which one of three identical containers was baited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…This could potentially explain why the addition of a social cue did not improve recall performance. As such, our results suggest that using experimenter identity as a social cue may be of limited effect at retrieval, especially in the presence of other more unique and diagnostic cues, something that is consistent with other work ( [49], MJ Beran 2016, personal communication).…”
Section: Discussionsupporting
confidence: 91%
“…This could potentially explain why the addition of a social cue did not improve recall performance. As such, our results suggest that using experimenter identity as a social cue may be of limited effect at retrieval, especially in the presence of other more unique and diagnostic cues, something that is consistent with other work ( [49], MJ Beran 2016, personal communication).…”
Section: Discussionsupporting
confidence: 91%
“…Third, the low probability and high unpredictability of encountering mid- to large-sized felid predators, which live at low densities in large ranges, are likely to make an encounter and its corresponding response by the mother an unusual event. Considering that unusual and emotionally laden events are more memorable than usual and neutral events, it is conceivable that orangutan youngsters could make this association ( 35 , 36 ). Fourth, a growing body of evidence for episodic-like and event memory in nonhuman primates ( 37 ) and human infants [who, at the age of 17 months, remember temporally ordered sequences of events and actions after a delay period of 6 weeks ( 38 )] suggests that displaced reference might enable learning in young orangutans.…”
Section: Resultsmentioning
confidence: 99%
“…Examining distinctiveness (Hunt & Worthen, 2006;Hunt & Smith, 1996), Lewis, Call, and Berntsen (2017a) demonstrated that apes can remember a distinctive event when probed by features that overlap with the distinctive event ( Figure 1, Cue environment 3). Apes remembered which container food had previously been hidden under when presented with cues that occurred during the hiding event, but only when the event was distinctive.…”
Section: Spontaneous Memories In Apesmentioning
confidence: 99%
“…As there were three containers, chance was 33%. (*p<0.05) (Adapted fromLewis et al, 2017a). is the author's version of a work that was accepted for publication in Current Directions in Psychological Science.…”
mentioning
confidence: 99%